2016
DOI: 10.1177/0892705715570988
|View full text |Cite
|
Sign up to set email alerts
|

A study on cutting temperature for wood–plastic composite

Abstract: Wood–plastic composite (WPC) material has been developed rapidly and used widely to replace wood production in recent years. The cutting process of WPC material is the key to directly affect the efficiency of utilization and processing. The infrared thermal imaging system and numerical control machine tool were used in this article to analyze the cutting temperature under different cutting parameters, which was further compared with massoniana wood cutting procedure to provide theoretical basis for WPC materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
(7 reference statements)
1
10
0
Order By: Relevance
“…As the cutting tool removes the unwanted material, chips take away most of the heat, while a small fraction of the heat remains on the tool surface and is dissipated into ambient air. This finding agrees with the work by Pei et al [13], which investigated cutting heat of WPC milling. Furthermore, the temperatures of the cutting edge and the chips had trends similar to the cutting forces; WPPC exhibited the highest cutting temperature, followed by WPEC and WPVCC.…”
Section: Effects Of Wood-plastic Composite Types On Cutting Temperaturesupporting
confidence: 93%
See 1 more Smart Citation
“…As the cutting tool removes the unwanted material, chips take away most of the heat, while a small fraction of the heat remains on the tool surface and is dissipated into ambient air. This finding agrees with the work by Pei et al [13], which investigated cutting heat of WPC milling. Furthermore, the temperatures of the cutting edge and the chips had trends similar to the cutting forces; WPPC exhibited the highest cutting temperature, followed by WPEC and WPVCC.…”
Section: Effects Of Wood-plastic Composite Types On Cutting Temperaturesupporting
confidence: 93%
“…Shi et al [12] investigated variations in chip size during WPC milling and found that while thickness was positively correlated with feed speed, the opposite was true for cutting speed. Through a systematic study which considered multiple process factors, Pei et al [13] confirmed that cutting depth contributed most to cutting temperature, followed by spindle speed and cutting width. Interestingly, they also found that most of the heat generated during cutting was taken away by the chips generated.…”
Section: Introductionmentioning
confidence: 99%
“…A wide breadth of papers covers subjects related to the multifarious utilization of forestry wastes and forest biomass from CE perspectives. Some of the recorded utilizations of biomass related to the following: sugars production, wood residues utilization as raw material for fertilizers and soil liming agent, utilization of by-products resulting from street trees' pruning operations for creation of insulation panels, use of fly ash from forest biomass combustion as a potential additive replacing calcite in cement-based mortars, and development of wood-plastic composite material and others [24,25,27,[31][32][33][34][35][36][37][38][39][40][41][42][43]. In the same framework, Voshell et al [28] explored forest and wood residues properties towards treatment and recycling.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…The results of the study by Pei et al (2016) showed that the cutting temperature increases with the increase of spindle speed and cutting depth, but decreases with the increase of feed rates. However, cutting parameters were selected higher than the usual ones.…”
Section: Introductionmentioning
confidence: 99%